2004
DOI: 10.1002/asi.20019
|View full text |Cite
|
Sign up to set email alerts
|

Information grounds and the use of need‐based services by immigrants in Queens, New York: A context‐based, outcome evaluation approach

Abstract: We elaborate on Pettigrew's (1998, 1999) theory of information grounds while using an outcome evaluation approach enriched by its focus on context to explore the use of need-based services by immigrants in New York City. Immigrants have substantial information and practical needs for help with adjusting to life in a new country. Because of differences in language, culture, and other factors such as access, new immigrants are a difficult population to study. As a result, little research has examined their predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
251
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(272 citation statements)
references
References 24 publications
6
251
0
4
Order By: Relevance
“…The few studies conducted on the role of public libraries in the lives of immigrants found that libraries facilitate and create contact between groups, for example between majority groups and minority groups and satisfy the basic information needs of newcomers (Elbeshausen and Skov, 2004;Fisher et al, 2004;Caidi and Allard, 2005;Audunson et al, 2011).…”
Section: Theoretical and Empirical Contributionsmentioning
confidence: 99%
“…The few studies conducted on the role of public libraries in the lives of immigrants found that libraries facilitate and create contact between groups, for example between majority groups and minority groups and satisfy the basic information needs of newcomers (Elbeshausen and Skov, 2004;Fisher et al, 2004;Caidi and Allard, 2005;Audunson et al, 2011).…”
Section: Theoretical and Empirical Contributionsmentioning
confidence: 99%
“…The literature on the relation between libraries and social inclusion highlights the contribution of libraries to the integration of minorities into local communities (Fisher, Durrance and Hinton 2004;Molz and Dain 1999), to serve information needs of homeless people and connect them to social services (Barbieux 2012;Lilienthal, 2011;Muggleton and Ruthven, 2011), to the reduction of juvenile delinquency (Naylor 1987), to the increasing literacy of both children and adults in particular in disadvantaged contexts (Adams, Krolak, Kupidura and Pahernik, 2002;Harding, 2013;Krolak, 2006), to the creation of "new" public spaces (Caidi and Davies 2005;Celano and Neuman 2001;Davies, Schwartz, Servon and Pinkett 2003). The majority of empirical studies carried out on the role of public libraries mainly focused on the perception of users about the library service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research done by [12] mentioned that the areas in which immigrant needed information were multitudinous as well. These needs, however, crystallized into the following major areas:…”
Section: Information Needs Of Migrant Workersmentioning
confidence: 99%
“…ICT includes fixed line telephones, mobile phones, radios, televisions, computers and internet access. These devices increasingly affect how we work and connect with each other, with whom they connect and how they make decisions, based on which information [12] [15]. The digital divide refers to the uneven distribution of information and communication technology (ICT) between and within nations [13].…”
Section: External Factors Of Information Seeking Behaviorsmentioning
confidence: 99%